1996
DOI: 10.1007/bf00192319
|View full text |Cite
|
Sign up to set email alerts
|

Straight forward to the queen: pursuing honeybee drones (Apis mellifera L.) adjust their body axis to the direction of the queen

Abstract: At a natural drone congregation area freeflying drones were attracted by a fast-moving queen dummy and the pursuits of drones were stereoscopically recorded (Fig. 1). The reconstruction of 192 flight paths from successfully approaching drones in chronological three dimensional sequences (Fig. 4) lead to the following results: 1. The alignment of the drone's longitudinal body axis coincides fairly well with the line connecting drone and queen (drone-queen-axis), its mean angular deviation from this line being o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…(Koeniger, 1988). Recent experimental studies of flying drones attracted by a fast moving queen dummy revealed a surprising behavioral adaptability of the drone's strategy to different mating situations (Gries and Koeniger, 1996). Competition behavior of males which results in an active displacement of competitors from superior mating territories is quite common in species with male mating assemblies (lekking) and as a result of this the larger males usually occupy territories or locations where the probability of access to the females is optimal (Blum and Blum, 1979;Thornhill and Alcock, 1983;Alcock and Houston, 1987 (Loper et al, 1987;Vallet and Coles, 1993).…”
Section: Classification Of Drone Typementioning
confidence: 99%
See 1 more Smart Citation
“…(Koeniger, 1988). Recent experimental studies of flying drones attracted by a fast moving queen dummy revealed a surprising behavioral adaptability of the drone's strategy to different mating situations (Gries and Koeniger, 1996). Competition behavior of males which results in an active displacement of competitors from superior mating territories is quite common in species with male mating assemblies (lekking) and as a result of this the larger males usually occupy territories or locations where the probability of access to the females is optimal (Blum and Blum, 1979;Thornhill and Alcock, 1983;Alcock and Houston, 1987 (Loper et al, 1987;Vallet and Coles, 1993).…”
Section: Classification Of Drone Typementioning
confidence: 99%
“…There, the flying young queen is regularly followed by large swarms of drones which compete for mating (Gries and Koeniger, 1996). It is not known yet whether small drones follow a mating strategy which is different from the strategy of large drones.…”
Section: Introductionmentioning
confidence: 99%
“…These formations were termed "drone comets" or "mating comets". They build up and may disintegrate within seconds (Gary, 1962(Gary, , 1963van Praagh et al, 1980;Gries and Koeniger, 1996). No aggression within a comet was observed (Gary, 1963;Koeniger et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not only the sex pheromones that are important for mating behaviour, but the shape, colour and pattern of the queen dummy also play an important role (Gary and Marston, 1971;Koeniger, 1990;Vallet and Coles, 1993;Gries and Koeniger, 1996).…”
Section: Example 2: Acute Effects Of Sublethal Doses Of Insecticides mentioning
confidence: 99%
“…The queen or dummy has to be fixed on a third bar in an identical angle to both recorders (Gries and Koeniger, 1996). Examples of possible research goals and their respective methods are given in Table 6.…”
Section: Experiments With the Mastmentioning
confidence: 99%